Teachers, ideas, and readings that shaped the thought of Charles Robert Darwin - Priora, Juan Carlos (2013)
This paper sets out to review Charles Darwin’s teachers, readings, and which ideas and other events had a definite impact on his mental framework, to the extent that they prompted him to dismiss some ideas while adopting others. When discussing Charles Darwin, we will devote to his ancestors, studies, teachers, friendships, readings, and the doubts that nagged him throughout his life. In short, we will refer to the whole collection of the personal experiences that shaped and transformed his thought, to the point of prompting him to write a book that shook up the world.